Study of the possibilities of using a 6-minute rowing on a Concept2 ergometer to assess the level of endurance in students - Irina Bondarenko; Mykola Mintz; Yuri Sergienko; Ivan Golovachenko; Oleg Bondarenko; Gennady Kurasa (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to study the possibilities of using 6-minute rowing on a Concept2 ergometer in physical education of students with determining the distance that students overcome and develop a scale for assessing the level of endurance. Material & Methods: students of the Pyotr Mogila Black Sea State University (Mykolaiv) (n=200) participated in the study, among them 125 students from Ukraine (n=69 young men; n=56 girls) and 75 students from India (n=48 boys; n=27 girls). Testing was carried out on Concept2 rowing ergometers at the water sports complex. Methods used: analysis of scientific sources, analogy method, pedagogical testing, anthropometric measurements and methods of mathematical statistics. Results: use of a 6-minute walking test was examined to determine functionality; the use of rowing ergometers to determine the time for which students can cover a distance of 1000 m, 500 m. We proposed the use of Concept2 ergometers to assess the level of endurance of students, we developed a 5-point scale: we determined the length of the distance that students covered in 6 minutes of rowing on an ergometer. The differences in the physical development of students from Ukraine and India are determined. Conclusions: the possibility of using rowing ergometers in the system of physical education of students is confirmed. The correlation between body weight and the length of the distance that students covered in 6 minutes on a rowing ergometer was revealed. Attention is drawn to the differences in the distance length indicators (m), which students of India (1210,50±113,40) and Ukraine overcame (1391,32±113,69).